1991
DOI: 10.1039/c39910000121
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the ruthenium imido complexes, [Ru(η-C6H6)(N-2,6-R2C6H3)]2(R = Prior Me), and the crystal structure of [Ru(η-C6H6)(N-2,6-Pri2C6H3)]2

Abstract: Ruthenium imido complexes, [ ( T -C ~HMe 2), have been synthesised by the room temperature reaction of [(q-C6ti6)R~C12]2 with 2 equiv. of LiNH(2,6-R2C6H3) and 1 has been shown by single-crystal X-ray diffraction to be a symmetrical, imido-bridged dimer containing a bent Ru2N2 bridge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Furthermore, the addition of aryl azides to the solution provided ruthenium 1,4-diaryltetraazadiene complexes ( 7a – c ). Although several ruthenium complexes containing imido ligands have been reported, which are coordinated to one or two ruthenium centers, , only one cyclopentadienyl ruthenium imido complex, [Cp^RuCl­(NAd)] (Ad = adamantyl), has been reported by Severin and co-workers without reactivity investigation . This result inspired us that the use of bulky aryl azides would give the ruthenium imido complexes, which are less sterically congested than the corresponding ruthenium tetraazadiene complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the addition of aryl azides to the solution provided ruthenium 1,4-diaryltetraazadiene complexes ( 7a – c ). Although several ruthenium complexes containing imido ligands have been reported, which are coordinated to one or two ruthenium centers, , only one cyclopentadienyl ruthenium imido complex, [Cp^RuCl­(NAd)] (Ad = adamantyl), has been reported by Severin and co-workers without reactivity investigation . This result inspired us that the use of bulky aryl azides would give the ruthenium imido complexes, which are less sterically congested than the corresponding ruthenium tetraazadiene complexes.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure has been shown to be useful in the synthesis of ruthenium compounds, but the yields are somewhat lower and the products from initial studies were clearly dimeric. 7 The ability to influence the preference for imido ligand bridging has been demon- strated a number of times and appears to be strongly dependent upon the steric requirements of the groups on the imido. 8 In the synthesis of d 6 terminal imido complexes of ruthenium both the size of the η 6 -arene and the organic group on the imido can be changed to adjust the steric pressure at the metal center.…”
Section: Resultsmentioning
confidence: 99%
“…6 The ruthenium analogue of the d 6 osmium complexes appeared to form bridged complexes. 7 Previous work has shown that the preference for bridged or monomeric imido complexes can be controlled by adjusting the steric requirements of the ancillary ligands or the organic group on the imido ligand. 8 Using a more sterically demanding imido ligand, it is possible to isolate complexes that contain monomeric imidos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the lone pairs on nitrogen are probably involved in delocalized bonding with vacant metal orbitals; the Ru-Ru distance of 0.277 7(3) nm is also consistent with a direct metal-metal bond. 87 In contrast, similar reactions of bulky LiNHAr derivatives with [{OSC1 2 (T|-arene) } 2 ] (arene = cym, C 6 Me 6 ) give monomeric imido complexes [Os(NR)(rj-arene)] (R = Bu 1 *, 2,6-C 6 H 3 Pr i 2 , 2,6-C 6 H 3 Me 2 ). In the NBu 1 derivative, the Os-N-C unit is almost linear and the Os-N distance (0.173 7(7) nm) is consistent with an Os=N triple bond arising from N(p w ) to Os(d) interaction.…”
Section: Complexes Of Ruthenium and Osmium Containing Rj -N Hydrocarbmentioning
confidence: 92%